Ischemia‐responsive protein 94 is a key mediator of ischemic neuronal injury‐induced microglial activation. Issue 6 (31st July 2017) - Tikamdas, Rajiv; Singhal, Sarthak; Zhang, Ping; Smith, Justin A.; Krause, Eric G.; Stevens, Stanley M.; Song, Sihong; Liu, Bin
Abstract : We proposed the following cascade for neuron‐microglia interplay in ischemic injury: mild neuronal injury occurring in the early stage of an ischemic event causes the release of neuronal factors including Irp94 which induce the activation of microglia that release toxic factors to exacerbate neuronal damage through the creation of a vicious cycle of neuronal injury and microglial activation. We think that validation of this hypothesis in vivo could eventually lead to Irp94‐related novel diagnostic and/or interventional strategies in the management of ischemic brain injury. Abstract: Neuroinflammation, especially activation of microglia, the key immune cells in the brain, has been proposed to contribute to the pathogenesis of ischemic stroke. However, the dynamics and the potential mediators of microglial activation following ischemic neuronal injury are not well understood. In this study, using oxygen/glucose deprivation and reoxygenation with neuronal and microglial cell cultures as an in vitro model of ischemic neuronal injury, we set out to identify neuronal factors released from injured neurons that are capable of inducing microglial activation. Conditioned media (CM) from hippocampal and cortical neurons exposed to oxygen/glucose deprivation and reoxygenation induced significant activation of microglial cells as well as primary microglia, evidenced by up‐regulation of inducible nitric oxide synthase, increased production of nitrite and reactive oxygen species, and increased expression of microglial markers. Mechanistically, neuronal ischemia‐responsive protein 94 (Irp94) was a key contributor to microglial activation since significant increase in Irp94 was detected in the neuronal CM following ischemic insult and immunodepletion of Irp94 rendered ischemic neuronal CM ineffective in inducing microglial activation. Ischemic insult‐augmented oxidative stress was a major facilitator of neuronal Irp94 release, and pharmacological inhibition of NADPH oxidase significantly reduced the ischemic injury–induced neuronal reactive oxygen species production and Irp94 release. Taken together, these results indicate that neuronal Irp94 may play a pivotal role in the propagation of ischemic neuronal damage. Continued studies may help identify Irp94 and/or related proteins as potential therapeutic targets and/or diagnostic/prognostic biomarkers for managing ischemia‐associated brain disorders.